FK506-binding protein 5 inhibits proliferation and stimulates apoptosis of glioma cells - Yang, Hui (Arch Med Sci, 2015)
INTRODUCTION: FK506-binding protein 5 (FKBP5) is reported to act as a scaffolding protein for Akt to promote the dephosphorylation of AKT Ser473 and suppress pancreatic cancer growth. However, other studies have shown that FKBP5 promotes tumor growth and chemoresistance through regulating NF-κB signaling in other cancers. In this study, we attempted to investigate the role and mechanism of action of FKBP5 in the regulation of proliferation and apoptosis of glioma cells. MATERIAL AND METHODS: The glioma U251 cell line was used as the model. Cell proliferation was detected by MTT assay. Cell apoptosis was detected by annexin-V staining. Protein expression was detected by Western blot analysis. RESULTS: FKBP5 overexpression inhibited the proliferation of U251 cells significantly (p < 0.05), and promoted the apoptosis of U251 cells significantly (p < 0.05). In addition, FKBP5 overexpression inhibited the phosphorylation of Akt at Ser743, decreased the level of Bcl-2, increased the level of Bax, and enhanced the cleavage of caspase-9 and caspase-3 (p < 0.05 compared to control). In contrast, FKBP5 knockdown enhanced the proliferation of U251 cells, increased the phosphorylation of Akt significantly (p < 0.05), increased the expression of Bcl-2 and decreased the expression of Bax, and decreased the cleavage of caspase-9 and caspase-3 significantly (p < 0.05). CONCLUSIONS: FKBP5 plays the role of a tumor suppressor in glioma by inhibiting the activation of Akt and stimulating the intrinsic mitochondrial apoptotic pathway, and could be used as a new target for gene therapy of glioma.